Radar estimation of precipitation around Madras (MAUSAM, 1982)
Radar observations over a selected target area of 2000 sq km near Madras were compared with data from a recording raingauge network. A mean relationship for northeast monsoon rains not associated with cyclones between radar reflectivity factor (Z) and rainfall rate (R) was derived. The constants in the Z-R equation are found to be appreciably lower than the Marshall-Palmer values. This mean relationship may not hold good for each individual occasion of rainfall. A gauge to radar estimate ratio was therefore determined for each occasion over this small raingauge network and this ratio used to adjust radar estimates over larger areas. Such adjusted estimates of total areal rainfall over 17000 sq km area were found to agree within a factor of two with a net work of 50 non-recording raingauges. Spatial distribution of rainfall indicated by radar and by raingauges also agree well but point estimates do not show good agreement. It is concluded that total areal rainfall and spatial distribution of rainfall can be assessed over large areas by using a mean seasonal relationship and an adjustment factor derived for each occasion from a small raingauge network. The radar estimate can in turn be used as ground truth to adjust satellite estimates over larger areas.